Fenomena Penggunaan Media Sosial Tiktok Sebagai Eksistensi Diri: Studi Fenomenologi pada Karyawan di PT. Bencuan Jaya Indonesia - Tasya Azizah; Lina Wati; Ajeng Pradesti (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The problem in this study is how to use Tiktok social media as a self-existence and the motive for its use by employees at PT. Bencuan Jaya Indonesia. The purpose is to understand how Tiktok social media is used as self-existence and to find out the reasons/motives for using Tiktok social media as self-existence for employees at PT. Bencuan Jaya Indonesia. The theory that is considered relevant in this study is the Theory of Phenomenology by Alfred Schutz's thought. The data collection method is in the form of in-depth interviews, observations, and documentation. The main informants consisted of 3 employees at PT. Bencuan Jaya Indonesia. The results of the study show that the use of Tiktok through the content it uploads as its existence on Tiktok social media, through the content it uploads can be a means of entertainment and information for its followers so that its existence can be known by the public. The main motive for use is to show talent/hobbies, fill free time as well as the motive to increase popularity and become an affiliate/content creator.